Analisis Hasil Evaluasi Program AKM Kelas Kampus Mengajar 7 terhadap Kemampuan Literasi dan Numerasi di SDN Bades 03 - Cantika Kunthi Prabandari; Astri Widyaruli Anggraeni (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to evaluate the effectiveness of the AKM program of the Teaching Campus Class 7 in improving students' literacy and numeracy skills at SDN Bades 03. The research method used is literature research with a qualitative literature study approach. The data used are the results of the pretest and posttest of students' literacy and numeracy before and after participating in the program. The results of the analysis showed that there was a significant improvement in students' numeracy skills, from an average pretest score of 34.4% to 50.1% in the posttest. Meanwhile, the increase in literacy skills, although positive, was relatively small, from 50.1% to 54.6%. These findings show that this program is effective in improving students' basic skills, especially in the aspect of numeracy. Factors supporting the success of the program include interactive teaching methods and support from teachers as well as the use of relevant teaching materials. In conclusion, the AKM Teaching Campus Class 7 program has succeeded in making a positive contribution in improving students' basic competencies, but further evaluation of literacy teaching methods is needed to achieve more optimal results. The implications of this study emphasize the importance of an adaptive and student-centered learning approach to improve the effectiveness of education in primary schools.